Biomedical Optics 2016 2016
DOI: 10.1364/ots.2016.om4c.6
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Unanesthetized Cerebral Oxygen Consumption Measures: Comparison of NIRS and MRI Approaches in Neonates with Congenital Heart Disease

Abstract: Cerebral perfusion in neonates with congenital heart disease is a clinical concern. Combined measures of MRI and NIRS can provide complementary information to improve monitoring. We compare multimodal measures of cerebral hemodynamics in this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…With recent advances of MRI, quantitative measurement of cerebral oxygen metabolism has shown clinical utility in several neonatal diseases. For instance, decreased CMRO 2 has been shown in neonates with congenital heart disease by two independent studies, and has also been demonstrated in neonates with punctate white matter lesions . Neonates with HIE have been reported to have lower oxygen extraction fraction than normal controls .…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…With recent advances of MRI, quantitative measurement of cerebral oxygen metabolism has shown clinical utility in several neonatal diseases. For instance, decreased CMRO 2 has been shown in neonates with congenital heart disease by two independent studies, and has also been demonstrated in neonates with punctate white matter lesions . Neonates with HIE have been reported to have lower oxygen extraction fraction than normal controls .…”
Section: Discussionmentioning
confidence: 93%
“…The sequence was performed using parameters determined in the optimization study, and three eTEs (0, 40, and 80 ms) with four repetitions were employed. Scan time of aTRUPC MRI was 3 min 44 s. For validation purposes, Y v measured by aTRUPC at the posterior superior sagittal sinus (SSS) was compared to that measured by a global technique, TRUST MRI . The TRUST sequence used parameters established previously: imaging slice was positioned 10 mm above the sinus confluence, TR = 3000 ms, TE = 8.3 ms, TI = 1020 ms; field of view = 160 × 160 × 5 mm 3 , voxel size = 2.5 × 2.5 × 5 mm 3 ; labeling slab thickness = 65 mm; 4 eTEs: 0, 40, 80, and 160 ms, scan time = 1.2 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…200 Note that oxygen is delivered to the fetus from the placenta through the umbilical vein, which was reported to have an average oxygenation of 84%. 202 For newborn infants, several MRI techniques have been adapted to measure OEF in the neonatal brain, including T 2 -based 57,62,[203][204][205] and phase-based 206…”
Section: Oef Across the Human Lifespanmentioning
confidence: 99%